Performance e símbolo: Uma análise da Folia de Reis - Figueiredo, William Bezerra (2013)
The revelry of kings, a procession of popular culture, recreates the official liturgies from the transgression of instituted values. The performance of revelers is subject to the study in order to reflect on the social roles and the experience of the sacred, looking for the subjective transformations of great impact among the community members which seeks to cure and heal the suffering in daily life. This soteriological aspect is approached from two theoretical fields that comes in dialogue. On the one hand the philosophy, from hermeneutics and phenomenology of religion, represented by Paul Ricoeur and Mircea Eliade. On the other hand the anthropology and the theatrical theories presented here under the names of Richard Schechner, Victor Turner, Eugenio Barba etc. These two theoretical features dialogue based on a methodology inspired by Paul Ricoeur, where we start from the concept of triple mimesis as a discursive structure. Starting from the prior or pre-figuration world, passing through the world of fiction or configuration and finally arriving at the world of life or refiguration (the world of the reader). In this theoretical background we find approximations and distances that enabled to rearrange new theoretical approaches, which considerably contribute to analyze the revelry of kings, from this theoretical world, opening new perspectives for its understanding.